(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This paper analyses today’s corruption context on Brazilian law and brings some figures regarding its impact on population’s daily life. It also seeks to identify the phenomenon taking into consideration the social and economical development of the country. In a first analysis, it looks into the social impact of the problem, which evolved to the creation of the Anticorruption Law number 12.846/2013. This law defined legally corruption in Brazil. In a second one, it identifies in which way Brazilian nation is prejudiced by corrupt acts, in social and economical terms. At last, it concludes stating some of the effects of corruption as a halt to development.